ANALYSIS OF BRAND AWARENESS AND CELEBRITY ENDORSER ON THE PURCHASE DECISION OF WARDAH COSMETIC PRODUCTS - Hardianawati Hardianawati; Karina Sukandi; Marisi Pakpahan (Faculty of Economics and Business Universitas Pelita Harapan, 2022)
The purpose of this study was to analyze how the influence of Brand Awareness and Celebrity Endorser on the Purchase Decision of Wardah cosmetic products (IBM asmi Student Study). The variable indicators of brand awareness are not recognizing the brand, brand recognition, brand recall, and peak of mind. Celebrity endorser variable indicators are trustworthiness (trustworthy), expertise (expertise), and attractiveness (attractiveness), while purchasing decision indicators are need recognition, information search, evaluation, purchase decision, post-purchase behavior. The population in this study is an IBM S1 student. The number of samples in this study taken based on Roscoe's theory with a minimum of 30-500 people, so 60 respondents obtained. The data analysis methods used in this research are validity test, reliability test, classical assumption test, multiple linear regression analysis, correlation coefficient analysis (R), determinant coefficient analysis (R2), partial hypothesis analysis (t-test) and simultaneous (f-test). The results of the analysis show that brand awareness has a partial effect on purchasing decisions. Celebrity endorsers have no partial effect on purchasing decisions. However, brand awareness and celebrity endorsers have a simultaneous effect on purchasing decisions. Purchasing decisions explained by the variable brand awareness and celebrity endorser by 62.4% and the remaining 37.6% explained by other variables outside this study.